2007
DOI: 10.1016/j.ijgo.2007.07.026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of iron supplementation on serum copper and zinc levels in pregnant women with high‐normal hemoglobin

Abstract: Iron supplementation in pregnant women with hemoglobin greater than 13.2 g/dL reduces serum levels of copper and zinc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…On the other hand, O'Brien et al [23] reported that administration of 60 mg of iron and 250 μg of folate without zinc supplementation during pregnancy caused a reduction of plasma zinc concentration; they therefore recommended the inclusion of zinc in prenatal supplements in order to reduce the potential of iron supplementation to adversely influence zinc status. Iron supplementation in pregnant women with haemoglobin greater than 13.2 g/dL reduces serum levels of copper and zinc [26]. Generally, zinc and copper deficiencies during pregnancy are associated with preeclampsia, low birth weight and poor foetal outcomes [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, O'Brien et al [23] reported that administration of 60 mg of iron and 250 μg of folate without zinc supplementation during pregnancy caused a reduction of plasma zinc concentration; they therefore recommended the inclusion of zinc in prenatal supplements in order to reduce the potential of iron supplementation to adversely influence zinc status. Iron supplementation in pregnant women with haemoglobin greater than 13.2 g/dL reduces serum levels of copper and zinc [26]. Generally, zinc and copper deficiencies during pregnancy are associated with preeclampsia, low birth weight and poor foetal outcomes [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Third, iron overload may impair the systemic response to inflammation and infection (1), which could be associated with adverse birth outcomes (50,51). Finally, there is also the potential for excess iron to alter the maternal gut microbiome (52) as well as increase the risk of copper and zinc deficiency (53), which may have implications for birth outcomes (54,55).…”
Section: Potential Mechanisms For Adverse Effects Of Excess Iron Durimentioning
confidence: 99%
“…High Fe intakes (another commonly used mineral supplement), particularly if coupled with low dietary Cu intake, can also lower Cu status. Recent evidence shows that supplementation of Fe to pregnant women who have good Fe status can reduce serum Cu, increase the risk for hypertension in the mother, and increase the incidence of small‐for‐gestational age in the offspring, arguing against indiscriminate Fe supplementation during pregnancy [25, 26]. Fe supplements can also reduce indices of Cu status in breastfed infants [27] and increase morbidity [28].…”
Section: Secondary Cu Deficienciesmentioning
confidence: 99%